Synthesis and Biological Evaluation of Some New Chalcones and Their Derivatives - Solankee, Anjani; Kapadia, Kishor; Thakor, Indrajit; Patel, Jayesh; Lad, Smruti (Asian Journal of Chemistry, 2016)
Some new chalcones have been prepared by the Claisen-Schmidt condensation between ketone and different aldehydes. Further chalcones on cyclocondensation with phenylhydrazine hydrochloride and thiourea in presence of alkali give pyrazolines and pyrimidinethiones respectively. The constitution of the synthesized products have been characterized by elemental analysis, IR and PMR spectral data. The products have been screened for their in vitro biological assay like antibacterial activity.